2011
DOI: 10.1002/j.0022-0337.2011.75.9.tb05164.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Pilot Bridging Program to Enable Australian Dental Therapists to Treat Adult Patients

Abstract: This study evaluated a pilot educational bridging program designed to provide dental therapists in Australia with the appropriate knowledge and skills required to enable them to translate their current clinical scope of practice to adult patients. Ten dental therapists completed a bridging program consisting of forty-two hours of didactic content, fourteen hours of clinical observation, forty-two hours of clinical practicum under direct supervision, and 105 hours of clinical experience with supervision by ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…No adverse impact on patient safety was reported in any of the included studies. Calache and Hopcraft undertook a descriptive study to determine the confidence level and knowledge of 10 dental therapists from Victoria in Australia trained in the management of adult patients . The results suggested that the educational program could provide the therapists with the knowledge and skills required to treat adult patients, but this was based on opinion only, and the numbers were limited.…”
Section: Resultsmentioning
confidence: 99%
“…No adverse impact on patient safety was reported in any of the included studies. Calache and Hopcraft undertook a descriptive study to determine the confidence level and knowledge of 10 dental therapists from Victoria in Australia trained in the management of adult patients . The results suggested that the educational program could provide the therapists with the knowledge and skills required to treat adult patients, but this was based on opinion only, and the numbers were limited.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, strategies could also be explored to improve access and reduce wait times for public dental services through the use of an alternative dental workforce such as dental therapists, oral health therapists, and dental hygienists. The use of this dental workforce can be a more costeffective way of providing preventative and non-complex oral health care to children and adults than relying predominantly on dentists [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…The educational bridging program was developed based on a review of the literature on educational models shown to be effective in changing clinician's performance or patient outcomes (19). The aim of the educational program was to enable participants to undertake clinical procedures already within the scope of practice for dental therapists on adult patients aged 26+ years, including oral examination, treatment planning, preventive management, and direct restorative treatment without the prescription or supervision of a dentist.…”
Section: Methodsmentioning
confidence: 99%
“…The educational program ran over a 6‐month period. The details of the curricula have been described in more detail elsewhere (19).…”
Section: Methodsmentioning
confidence: 99%